Pathogenicity of Highly Pathogenic Avian Influenza Virus (H5N1) in Adult Mute Swans - Donata Kalthoff; Angele Breithaupt; Jens P. Teifke; Anja Globig; Timm Harder; Thomas C. Mettenleiter; Martin Beer (Emerging Infectious Diseases, 2008)
Adult, healthy mute swans were experimentally infected with highly pathogenic avian influenza virus A/Cygnus cygnus/Germany/R65/2006 subtype H5N1. Immunologically naive birds died, whereas animals with preexisting, naturally acquired avian influenza virus–specific antibodies became infected asymptomatically and shed virus. Adult mute swans are highly susceptible, excrete virus, and can be clinically protected by preexposure immunity.